PENGEMBANGAN BAHAN AJAR BERBASIS CERITA BERGAMBAR PADA PEMBELAJARAN TEMATIK TERPADU DI KELAS 3 SDN 07 SIKABU MUNTO KECAMATAN SUTERA KABUPATEN PESISIR SELATAN - Melindawati, Silfi (Jurnal Riset Pendidikan Dasar Dan Karakter, 2023)
This research was conducted at SDN 07 Sikabu Munto on The Development of Pictorial Story-Based Teaching Materials in Integrated Thematic Learning in Grade 3 behind teacher learning using only LKS and student books as a source in delivering learning materials,students are sleepy and unfocused inlearning. The purpose of this study is to know the validity and practicality of pictorial story-based teaching materials. The research design used is research and development. This study sample was a 3rd grade elementary school student numbering 20 students. The data collection techniques in this study use expert validation sheets and practicality questionnaires of teachers and learners. The development of this teaching material uses microsoft word 2016 application. The selection of this application is based on its easy use. Validation results are obtained from 90% material experts with very decent categories, linguists 80% with decent categories, 90% design experts with very decent categories, and practicality tests by 3rd grade teachers with a percentage of 87% with very decent categories and by learners with a percentage of 89% very decent categories. So it can be concluded that The Pictorial Story-Based Teaching Material in Integrated Thematic Learning in Class 3 is very suitable for use in SDN 07 Sikabu Munto Kecamatan Sutera Kabupaten Pesisir Selatan.